Philosophy of Advanced Science "Ethics and Morals in Science" - Rahman, Muhammad Zaki; Syukri SS, Ahmad; Yenti, Zarfina (Jurnal Indonesia Sosial Sains, 2025)
Ethics and morals in science are two important aspects that guide the behavior of scientists and ensure that the development of science is carried out responsibly and beneficial to society. Ethics is related to moral principles that guide behavior in the scientific world, while morality emphasizes more on good and bad values in human actions, including in the context of science. The purpose of this writing is to find out the understanding related to the Meaning of Ethics and Morals in Science, Types/Types of Ethics and Morals, Philosophy of Utilitarianism Ethics, Ethics and Morals in Science, Ethics and Morals in Scientific and Humanities.